2020
DOI: 10.15252/msb.20209885
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide off‐rates reveal how DNA binding dynamics shape transcription factor function

Abstract: Protein– DNA interactions are dynamic, and these dynamics are an important aspect of chromatin‐associated processes such as transcription or replication. Due to a lack of methods to study on‐ and off‐rates across entire genomes, protein– DNA interaction dynamics have not been studied extensively. Here, we determine in vivo off‐rates for the Saccharomyces cerevisiae chromatin organizing factor Abf1, at 191 sites simultan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 120 publications
1
10
0
Order By: Relevance
“…While ChIP traditionally measures average TF occupancy (Fig. 1), recent modifications of the technique enable measurements of kinetic rates (k on , k off ):k on can be determined by varying the cross-linking duration (Poorey et al 2013), whereas measuring bound TFs at various time points after acute depletion of nuclear TFs provides access to genome-wide k off values (Jonge et al 2020). ChIP, however, is subject to two technical caveats: first, TFs can artificially dissociate from chromosomes upon cross-linking (Teves et al 2016;Festuccia et al 2019), which can be overcome by alternatives bypassing cross-linking (Skene and Henikoff 2017), and second, ChIP accuracy is limited by antibody quality (Shah et al 2018).…”
Section: In Vivo Binding Specificitymentioning
confidence: 99%
“…While ChIP traditionally measures average TF occupancy (Fig. 1), recent modifications of the technique enable measurements of kinetic rates (k on , k off ):k on can be determined by varying the cross-linking duration (Poorey et al 2013), whereas measuring bound TFs at various time points after acute depletion of nuclear TFs provides access to genome-wide k off values (Jonge et al 2020). ChIP, however, is subject to two technical caveats: first, TFs can artificially dissociate from chromosomes upon cross-linking (Teves et al 2016;Festuccia et al 2019), which can be overcome by alternatives bypassing cross-linking (Skene and Henikoff 2017), and second, ChIP accuracy is limited by antibody quality (Shah et al 2018).…”
Section: In Vivo Binding Specificitymentioning
confidence: 99%
“…The presence of multiple binding affinities is supported by an SMT study using an independent photobleaching correction approach that inferred up to six binding populations, rather than two ( 66 ). In line with these findings, determination of in vivo residence times with chromatin immunoprecipitation (ChIP)-based techniques showed that residence times differ extensively at different binding sites across the genome ( 67 , 68 ). Additionally, even at a single binding site, TF conformational changes or TF interactions with other transcriptional regulators can result in multiple binding states with different residence times and multi-exponential distributions, underscoring the challenges in interpretation of these residence times if the target loci are unknown.…”
Section: Main Textmentioning
confidence: 67%
“…[ 53 ] and de Jonge et al . [ 54 ], respectively. Chromatin remodelers influence binding of TFs to DNA and can thus influence gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular features incorporated in the integrated model included the number of regulating TFs, location of their binding sites, their mean expression and noise levels, SAGA/ TFIID dependence of genes for their expression [50], whether a gene was co-activator redundant or TFIID dependent [51], binding activity of several broadly acting TFs such as TBP, ABF1 and RAP1 [52][53][54], binding patterns of chromatin remodelers [55][56][57], histone levels, histone modification patterns and histone binding dynamics [58,59], three-dimensional genomic contacts [60], tRNA adaptation index [61], mRNA secondary structure, mRNA and protein half-lives [62][63][64], post-translational modifications [65], in addition to nucleosome occupancy pattern [66] and presence/absence of the TATA box sequence in the promoter [67]. For a gene, we only considered those TFs for which experimental evidence for DNA binding had been obtained or change in expression upon knocking out the TF had been experimentally observed.…”
Section: Molecular Features Associated With Tf Binding Were the Top P...mentioning
confidence: 99%
See 1 more Smart Citation